Numerical algorithm for moving-boundary fluid dynamics problems and its testing - Minakov, A. V. (Computational mathematics and mathematical physics, 2014)
A new Eulerian algorithm is proposed for computing incompressible flows with moving boundaries of arbitrary geometry. The algorithm can be regarded as an extension of Hirt’s classical volume-of-fluid method. The results of its implementation and testing are presented. A comparison of the numerical results with experimental data and computations of other authors reveals good agreement.